2019
DOI: 10.1159/000503451
|View full text |Cite
|
Sign up to set email alerts
|

Poor Diet, Stress, and Inactivity Converge to Form a “Perfect Storm” That Drives Alzheimer’s Disease Pathogenesis

Abstract: North American incidence of Alzheimer’s disease (AD) is expected to more than double over the coming generation. Although genetic factors surrounding the production and clearance of amyloid-β and phosphorylated tau proteins are known to be responsible for a subset of early-onset AD cases, they do not explain the pathogenesis of the far more prevalent sporadic late-onset variant of the disease. It is thus likely that lifestyle and environmental factors contribute to neurodegenerative processes implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 227 publications
0
15
0
Order By: Relevance
“…One typical pathological character of AD is the formation of senile plaques in the brain, which are induced by amyloid-β (Aβ) deposition and neurofibrillary tangles generated by exaggerated phosphorylation of tau protein within the neuron [8][9][10]. In addition, neuron loss and synaptic dysfunction mainly caused by senile plaques and neurofibrillary tangles are another crucial pathological feature of AD [11].…”
Section: Introductionmentioning
confidence: 99%
“…One typical pathological character of AD is the formation of senile plaques in the brain, which are induced by amyloid-β (Aβ) deposition and neurofibrillary tangles generated by exaggerated phosphorylation of tau protein within the neuron [8][9][10]. In addition, neuron loss and synaptic dysfunction mainly caused by senile plaques and neurofibrillary tangles are another crucial pathological feature of AD [11].…”
Section: Introductionmentioning
confidence: 99%
“…Males also showed an increase in pro-(IL-6, KC-GRO) and anti-(IL-5, IL-10) inflammatory peripheral cytokines after both the initial and final chronic injection of LPS. These effects are to be expected, as an initial immune challenge promotes the production and circulation of systemic inflammation in response to a challenge (Couper et al, 2008;Deslauriers et al, 2017;Pacholko et al, 2019;Pripp and Stanišić, 2014); however, the observed differences at the terminal endpoint suggest a more sustained impact on inflammatory regulation following chronic stress and chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Diet may also play a supportive role within the noradrenergic system as a preventing factor of neurodegenerative diseases. Indeed, poor and wrong diet-styles and their related neuroinflammatory consequences [140,141,142] are associated with worse prognosis and higher neurodegeneration risks [13, 140, 141 143, 144]. Interventions on diet may be beneficial to restore potential harmful micro and macro nutrient insufficiencies according to current guidelines for prevention [145].…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%